The effect of treatment for soil-transmitted helminthiasis on cognitive function in children - Dewi Sari; Muhammad Ali; Syahril Pasaribu (Paediatrica Indonesiana, 2012)
Background Soil-transmitted helminth (STH) infections affectone-third of the world's population. School-aged children arereported to have the highest prevalence and intensity of disease,resulting in impaired cognitive function, malnutrition andmorbidity.Objective To examine differences in cognitive function in STHinfectedchildren before and after treatment.Methods We conducted a randomized, open-label, controlled trialfrom November 2 008 - March 2009 in Aek Na bar a, Lab uh an BatuDistrict, North Sumatera Province. Subjects were primary schoolagedchildren with STH infection. Before intervention, data onage, sex, nutritional status, STH infection status and cognitivefunction were collected. Subjects were divided into two groupsby simple randomization. Group I received 400 mg albendazoleand group II received a placebo. Three months after intervention,cognitive function of subjects in both groups was reassessed. Datawas analysed by Student's t test, with P value of less than 0.05considered to be statistically significant.Results Cognitive tests with the Wechsler Intelligence Scale forChildren (WISC) were performed in 120 children infected withSTH. Sixty children received 400 mg albendazole and 60 childrenreceived placebo. Seven children were excluded and one droppedout from this study. Three months after the intervention, wereevaluated cognitive function and found significant differencesin the categories of digit span (P=0.024) and total IQ score(P=0.027) between the two groups.Conclusions Treatment of STH infection with albendazoleimproved cognitive function of children in comprehension, codingand digit span testing. Performance and full IQ scores were alsoimproved after treatment. [Paediatr lndones. 2012;52:99-105].